INDIGENOUS KNOWLEDGE FOR FOREST-MANAGEMENT AND CLIMATE CHANGE ADAPTATION IN FOREST DEPENDENT COMMUNITIES OF CROSS RIVER, NIGERIA (2015)
Climate change is a major global human development challenge. Modern technologies have been largely unsuccessful in tackling this challenge, thus indigenous knowledge for forest-management is being considered as an alternative solution. There is dearth of knowledge on the effects of cultural factors on climate change adaptation in forest-communities of Cross River, hence, this study examined the extent to which beliefs and practices of forest-management in forest-dependent communities of Cross River are engaged in addressing challenges of climate change. Ecological modernisation served as the theoretical framework while the research design was Participatory Rural Appraisal. A semi-structured questionnaire was used to collect information from 459 respondents purposively selected from three forest-dependent communities representing mangrove forest (Iko-Esai, 153), Ekuri forest (Agoi-Ibami, 191), and Mbe/Afi forest (Butatong, 115) blocks. Quantitative data collected was on socio-demographic characteristics, indigenous beliefs and practices, and their influence on climate change adaptation behaviour. Indigenous knowledge was assessed with an 8-item instrument which categorised indigenous forest-management practices into: zero-tilling, soil-mulching, bush-fallow, crop-rotation, green-manure, mixed-cropping, tree-felling, hunting taboos, and tree planting. Key Informant Interviews were conducted with 12 officials of the Ministry of Environment, and 33 In-Depth Interviews with 18 community leaders, seven forest managers, five academics, and three policy makers on forest-related traditions and practices. Climate change and transforming social structures were assessed through reviews of archives, reports and maps. Transects were used to identify similarities and differences of paths. Seasonal calendars assessed sequences of events and their relationship with the people; while institutional analysis assessed communities’ interests, layout, infrastructures, health and wealth patterns. Quantitative data were analysed using descriptive statistics and linear regression at p<0.05, while qualitative data were content analysed. The age of respondents was 40.5±4.5 years while 61.7% were males. Over 75.0% had lived in communities since birth, while 88.0% had a monthly income of less than N50,000. Effect of indigenous knowledge on climate change adaptation behaviour was significant (F=17.04; R=0.61; R2=0.37, Adj R2=0.35). Climate change adaptation behaviour was influenced by indigenous knowledge thus: use of fuel efficient cooking devices (β=0.34), seed exchange of early maturing crops (β=0.32), planting trees (β=0.27), poultry farming (β=0.13), bee keeping (β=-0.47), planting special species of crops (β=-0.30), migration to another community (β=-0.20), storing enough rainwater (β=-0.14), change period of planting crops (β=-0.13), fish farming (β=0.11). Indigenous forest-management practices occurred as: bush fallow (88%), mixed cropping (86%), green-manure (62%), tree-felling and hunting taboos (58%), tree planting (55%), soil mulching (53%), zero tilling (47%), and crop rotation (46%). Indigenous practices used to manage forests such as preservation of special species of trees, folklore on appeasement of forest gods, non-hunting of certain animals considered as agents of the gods, and non-sale of land were at risk of extinction. Oral tradition was the main source of disseminating indigenous knowledge, beliefs and practices. Indigenous knowledge and practices are useful in forest-management. Predominant climate change adaptation measures within forest-dependent Cross River are biased towards modern worldview. Therefore, the use of indigenous knowledge in forest-management should be strengthened in the policy process of climate change adaptation.